Influência de variáveis abióticas sobre a produção de sexuados em colônias da abelha melipona subnitida (apidae, meliponini) - Souza, Aline Oliveira de (Universidade Federal Rural do Semi-Árido, 2018)
In eusocial Hymenoptera, including bees, ants and wasps, colonies need to prioritize the production of workers and invest in production of sexual offspring (queens and males) without compromising the group survival. In semi-arid environments, such as the Caatinga biome in north-eastern Brazil, the abundance of food sources is extremely reduced during drought periods. Additionally, climatic conditions may limit the foraging activity of workers. Thus, food collectors leave the colony only when the environmental conditions are minimally suitable. The reduction of foraging activity influences the food intake into the colonies, which, in turn, influence the brood production of the colonies. The aim of this study was to evaluate the short-, medium-, and long-term influence of abiotic parameters on sexual offspring production of stingless bee Melipona subnitida (Apidae, Meliponini). The abiotic parameters evaluated were: maximum and minimum environmental temperature (Tmax, Tmin); maximum and minimum relative humidity (URmax, URmin), and accumulated rainfall (CHUVA). The brood production of two colonies (A, B) of M. subnitida was monitored during two periods of data collection: April 08 to May 13, 2016, and April 13 to May 12, 2017. The possible influence of the abiotic parameters on production was analysed in three ways: (1) long-term influence, which considered differences between abiotic parameters and differences in breeding production between the first and second period; (2) medium-term influence, which is the relation between the production of each brood comb and the abiotic parameters during its construction; and (3) immediate influence, which is the relationship between the daily brood cells production and the abiotic parameters on each day of production. We found no influence of abiotic parameters on the brood production of colony B, whose males production was superior to colony A in both experimental periods. The high male production was presumably related to a temporary peak in worker reproduction, who are not fertilized, and, therefore, can only produce (haploid) males. It is possible that abiotic conditions have a reduced influence on the colonies brood production during periods with elevated worker reproduction, who take advantage of the chances of increasing individual fitness. Concerning the long-term influences of abiotic parameters, we observed an increase in male production by colony A in the second experimental period, which was characterised by lower ambient temperatures, higher precipitation, and higher relative humidity. This result was probably due to an elevated food supply under these conditions. Both the queen and worker production remained stable between the two periods. Concerning the medium-term influences of abiotic parameters, a warmer and wetter environment resulted in an increase in the production of queens and workers, whereas the production of males increased in a cooler and dry environment. The lower humidity and precipitation conditions, less favourable to the food supply in the Caatinga, presumably leads to an increase in the number of workers within the nest owing to a temporal reduction of foraging activity. This may diminish the queen's control over brood production and can be used by workers as an opportunity to lay reproductive eggs, increasing the production of males under such environmental conditions. There was no immediate influence of abiotic parameters on brood production. Our analysis demonstrates the influence of abiotic parameters on the production of queens, males and workers of M. subnitida. However, this influence occurs in different ways according to the time scale considered and depends on colony intrinsic conditions
Keywords: Insetos eusociais; Abelha sem ferrão; Produção de cria; Operárias reprodutoras; Eusocial insects; Stingless bees; Environmental parameters; Breeding production; Reproductive workers; CIENCIAS BIOLOGICAS::ECOLOGIA